PENGARUH KOMPETENSI DAN DISIPLIN KERJA TERHADAP KINERJA PEGAWAI PADA KANTOR DINAS PERHUBUNGAN KOTA PALU - GHAZALI, RAHMAT (Fakultas Ekonomi Universitas Tadulako, 2016)
The purposes of this study are: 1) to determine and analyze the influence of competence and work discipline on the performance of employees at the Department of Transportation in Palu City; 2) to determine and analyze the influence of competence on the performance of employees at the Department of Transportation, Palu City; 3) to determine and analyze the influence of work discipline on the performance of employees at the Department of Transportation, Palu City. The sample of study consists of 56 people. Method of data analysis is multiple linear regressions with regression equation model as follows: Y = 1.070 + 0.635X1 + 0.152X2. The result of the simultaneous test shows that the competence and work discipline have positive and significant influence on the employees? performance. Partial test shows the competence variable has a positive and significant influence on employees? performance, while work discipline has positive and non-significant influence on employees? performance. The coefficient of determination shows the value of R-Square of 0.649, which shows that 64.9% employees? performance influenced by the competence and work discipline variables, and 35.1% influenced by other variables that are not examined in this study.